Yiddish: biography of a language - Shandler, Jeffrey (Oxford University Press, 2020)
"This book provides an introduction to Yiddish, the foundational vernacular of Ashkenazi Jews, both as a subject of interest in its own right and for the distinctive issues that Yiddish raises for the study of languages generally, including language diaspora, language fusion, multilingualism, language ideologies, and postvernacularity. By approaching the study of Yiddish through the rubric of a biography, rather than following a more conventional chronological, geographical, or ideological approach, this book examines the story of Yiddish thematically. Each chapter addresses a different "biographical" topic concerning the character of the language and how it has been conceptualized, ranging across time, space, and speech communities. These chapters interrelate discussions of the language's origins, characteristics, and development with the dynamics of its implementation in Ashkenazi culture from the Middle Ages to the present. These thematic chapters also examine the symbolic investments that both Jews and others have made in Yiddish over time, which are key to understanding both general perceptions and scholarly analyses of the language, especially in the modern period"--